Monetarism and the Aggregate Economy: Some Longer-Run Evidence - Turnovsky, Stephen J.; Wohar, Mark E. (The Review of Economics and Statistics, 1984)
A simple macro model is used to investigate various monetarist propositions over the period 1923-82. Initial tests indicate a structural break over this period and the subperiods 1923-60 and 1961-82 are analyzed separately. Results obtained for the latter period support the monetarist propositions put forward by Stein and others. However, upon closer investigation it appears that the crucial long-run neutrality that characterizes these findings is essentially generated by government policy and is not necessarily an intrinsic property of the economy over that period. By contrast, results obtained for the period 1923-60 are much less supportive of these same propositions.